A Randomized Clinical Study of a Curcumin and Melatonin Toothpaste Against Periodontal Bacteria - Riccardo Pulcini; Antonio Maria Chiarelli; Bruna Sinjari; Jessica Elisabetta Esposito; Francesco Avolio; Riccardo Martinotti; Vittorio Pignatelli; Luca Pignatelli; Laura Berlincioni; Stefano Martinotti; Elena Toniato (Biomedicines)
Background: The mouth and the oropharyngeal system are home to numerous bacterial species that constitute the so-called oral microbiome and play an important role for the integrity of the oral cavity, influencing the overall health of the body, as demonstrated by several studies. The aim of this study was to evaluate the bacterial modulation potential of a toothpaste (bioredoxin) containing curcumin and melatonin. Both substances have anti-inflammatory properties, as documented in several scientific reports. Methods: The in vivo study we present was a single-center, double-blind trial and was conducted in parallel groups. We enlisted 20 volunteers who were randomly assigned to four distinct groups using blinded four different toothpaste preparations: a standard toothpaste indicated as placebo, a toothpaste with curcumin, a toothpaste with melatonin, and a toothpaste with melatonin and curcumin. Results: The samples from the gingival tasks were taken at time 0 and after 8 weeks of toothpaste treatment. By evaluating the DNA content of the most significant periodontal bacteria related to the total bacteria count using quantitative PCR assays, including the saprophyte component of the microbiome, we demonstrated that the Curcumin and Melatonin treatment has a statistically relevant effect on decreasing the level of periodontal pathogenic bacteria DNA. The toothpaste with the addition of curcumin and melatonin showed a modulation between t0 and t1 of the Campylobacter rectus (14,568 vs. 3532.8) and Peptostreptococcus micro (1320.8 vs. 319) bacteria. In addition, a modulation of pathogenic bacteria and saprophytic bacteria was shown. The synergistic action of the two additives would therefore appear to lead to promising results. Conclusions: Despite the fact that additional studies may be necessary in evaluating the effect of the Curcumin/melatonin combination in modulating a proposed therapeutic effect on infections of the oropharyngeal apparatus, in this report, we show for the first time that a combination of curcumin and melatonin supplemented using an oral cosmetic vehicle has the capacity to decrease the level of periodontal pathogenic bacteria, possibly ameliorating health and the physiological conditions in the buccal scenario.